AI tools functions in education: A narrative overview - Mansor, Farah Ahlami; Hashim, Mimi Zazira; Wan Azib, Wan Nor Hazimah; Muhammad, Norrini; Mohd Firdaus Kozako5, Intan Nurul’ain (International Journal of Accounting, Finance and Business, 2025)
Artificial Intelligence (AI) is now being applied in the field of education, leading to significant improvements compared to traditional methods. Learning activities are becoming more stimulating and engaging than in the past. This paper highlighted eight functions of AI Tools in education consists of Intelligent Tutoring Systems (ITS), AI Algorithm, Virtual Reality (VR) and Augmented Reality (AR), Natural Language Processing (NLP), Educational Data Mining (EDM), Learning Analytics (LA), and Multimodal learning analytics (MMLA). The AI-assisted tool offers numerous impressive results and potential, enhancing learning experiences with an abundance of advantages. AI tools in education enable tailored educational adventures by identifying the abilities and shortcomings of learners, customizing the educational program, and modifying curriculum to meet specific demands. Individualized teaching permits learners to move forward at their own velocity, which leads to a greater understanding of the subject at hand. Artificial intelligence (AI) technologies boost evaluation procedures by automating assessments giving immediate responses to learners, while assisting learners in quickly determining opportunities for advancement. Although the advantages they offer, artificial intelligence (AI) tools in education bring security hazards arising from the acquisition of significant information about learners. It is critical to give priority to privacy and security of information to maintain confidence among educators, and learners, along with systems powered by AI. Furthermore, educators require proper guidance and assistance to effectively incorporate AI tools throughout the learning environment. Educators should develop the fundamental skills necessary to utilize advanced technologies and integrate them into their teaching methods. AI solutions can replace traditional educational methods via designed education, comprehensive evaluations, and informative material delivery. Overcoming issues with privacy and providing sufficient support for educators are key measures for maximizing the positive aspects of AI in education.